Understanding Linguistic Prejudice Critical Approaches to Language Diversity in Brazil - Massini-Cagliari, Gladis; Berlinck, Rosane Andrade; Rodrigues, Angelica (Springer International Publishing : Imprint: Springer, 2023)
XX, 202 p. 35 illus., 31 illus. in color.